Analysis of ASEAN-China Free Trade Area (ACFTA) Cooperation from a Competitive Intelligence Perspective - Abimanyu Hendi Asyono; Palupi Lindiasari Samputra (International Journal of Social Service and Research, 2023)
More than a decade has passed when the ASEAN-China Free Trade Area (ACFTA) first began, but until now many parties see ACFTA has not significantly impacted Indonesia's interests. This paper seeks to examine more deeply the position of the Indonesian economy in the midst of ACFTA's journey. Using a qualitative approach, this paper uses a descriptive method that explores ACFTA problems against Indonesian interests. The theoretical concept used in conducting analysis is from the point of view of competitive intelligence. The results show that ACFTA as a whole poses more threats and challenges than direct positive impacts. Despite the main positive impact that can be obtained by implementing the free trade agreement (FTA), ACFTA over the past decade has not been able to create positive conditions in the Indonesia-China trade balance. Threats and challenges are even obtained by Indonesia, especially industry players and domestic commodity traders who must prepare for the arrival of a "flood" of products from China. However, in terms of geopolitics and geostrategy, ACFTA's sustainability will greatly affect the overall cooperative relationship between Indonesia and China.